2021
DOI: 10.1002/pbc.29048
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for vitamin D deficiency in long‐term childhood cancer survivors

Abstract: Background: Childhood cancer survivors (CCS) have increased risk of developing chronic health conditions, including musculoskeletal disorders. Little is known regarding vitamin D deficiency (VDD, <20 ng/ml) and its association with bone mineral density (BMD) in long-term CCS. We evaluated the prevalence and risk factors for VDD in a large, diverse population of long-term CCS, and examined the association between VDD and BMD in patients who underwent guideline-recommended dual-energy X-ray absorptiometry (DXA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…The main treatment-related risk factors for low BMD include C(S)RT (highquality evidence), 6,9,32,38,51,54,64,68 total body irradiation (TBI) (high-quality evidence), 9,45,54,64,65 and corticosteroids (administered as anti-cancer treatment, moderatequality evidence) 6,9,51,54,68 . Survivors treated with higher doses of C(S)RT (low-quality evidence) 32 and corticosteroids (moderate-quality evidence) 32,46,69 are at greater risk of low BMD.…”
Section: Treatment-related Risk Factors For Low Bmdmentioning
confidence: 99%
See 2 more Smart Citations
“…The main treatment-related risk factors for low BMD include C(S)RT (highquality evidence), 6,9,32,38,51,54,64,68 total body irradiation (TBI) (high-quality evidence), 9,45,54,64,65 and corticosteroids (administered as anti-cancer treatment, moderatequality evidence) 6,9,51,54,68 . Survivors treated with higher doses of C(S)RT (low-quality evidence) 32 and corticosteroids (moderate-quality evidence) 32,46,69 are at greater risk of low BMD.…”
Section: Treatment-related Risk Factors For Low Bmdmentioning
confidence: 99%
“…321-323 and 326-328). Survivor characteristics and health behaviors associated with low BMD include low BMI (high-quality evidence), 6,9,40,42,51,54,56,64,68,69 male sex (high-quality evidence), 6,9,32,[40][41][42]45,51,54,56,64,65,68 White race (moderate-quality evidence),40,41,51,65,68 lack of physical activity (moderate-quality evidence), 11,40,51,56 and current or prior smoking (moderate-quality evidence). 6,9,56,61 We found conflicting evidence for the association between alcohol consumption 61 and low BMD.…”
Section: Other Risk Factors For Low Bmdmentioning
confidence: 99%
See 1 more Smart Citation
“…The common alterations in both CCS and cancer patients during therapy are in the metabolism of calcium, vitamin D, and magnesium [ 39 ], key micronutrients for bone growth [ 46 ]. It has been reported that the 25% of pediatric cancer patients show deficiency of vitamin D [ 47 ] and this condition increases the risk of low BMD by more than 3-fold [ 48 ]. Vitamin D influences bone mass [ 49 ], by modulating the differentiation of bone cells and bone mineralization [ 50 ].…”
Section: Physiopathology Of Osteoporosis In Ccs: General Risk Factorsmentioning
confidence: 99%
“…There are few studies on vitamin D deficiency in CCSs. Previous studies have reported the prevalence of vitamin D deficiency in CCSs, varying from 14% to 48% [ 17 , 18 , 19 , 20 , 21 ]. Considering that there is limited information on vitamin D deficiency among CCSs in tropical regions with an abundance of sunlight, such as southern Thailand, this study aims to identify the prevalence and clinical risk factors of vitamin D deficiency in CCSs in southern Thailand.…”
Section: Introductionmentioning
confidence: 99%